Employee Performance of Work Training Center in Banda Aceh (A Study of Government Regulation’s Implementation Number 46 of 2011 concerning Performance Assessment of Civil Servants) - Lidya Tasza; Ismail (SIASAT, 2020)
This study aims to determine and analyze the assessment of State Civil Apparatus (ASN) work targets on Work Training Center (BLK) in Banda Aceh as well as to find out and analyze the work behavior of Work Training Center (BLK) in Banda Aceh in preparing a professional workforce. This study uses a qualitative approach with the type of descriptive research. Data collection is done through observation, interviews and document studies. The conclusion of the research shows that the work targets of employees at the Work Training Center (BLK) in Banda Aceh related to quantity, quality, time and cost indicate that the quantity of work is very much and does not reduce quality. While the time spent completing these activities varies greatly and depends on the program itself. Furthermore, related to the costs required to complete a job, it really depends on the proposal and also a realistic study. Then the Behavior of Employees at the Work Training Center (BLK) in Banda Aceh in conducting service orientation to the community and other parties by promoting equality, means that there is no difference in services provided to the community and also to other institutions.